2019
DOI: 10.5114/areh.2019.89821
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga in the modulation of heart rate variability in patients with breast cancer

Abstract: Introduction: The aim of this study was to examine the effect of yoga on heart rate variability in patients with breast cancer in an outpatient rehabilitation program. Material and methods: Eighty-four patients with breast cancer were eligible for this study. After the exclusion of 7 women, participants were randomly allocated to a yoga exercise program (group A, n=33) and Pilates exercise program (group B, n=44). Heart rate variability parameters were evaluated at baseline, after six and twelve months of yoga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Breast cancer patients showed improved HRV values at end of a 12-month long (3 times/week, 40-60 min/session) yoga training. These results were also significantly better than those of a Pilates control group (46). Similarly, patients with rheumatoid arthritis showed improved HRV values after a 12-week long (3 times/week, 30 min/session) yoga practice compared to the only medical treatment control group (45).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Breast cancer patients showed improved HRV values at end of a 12-month long (3 times/week, 40-60 min/session) yoga training. These results were also significantly better than those of a Pilates control group (46). Similarly, patients with rheumatoid arthritis showed improved HRV values after a 12-week long (3 times/week, 30 min/session) yoga practice compared to the only medical treatment control group (45).…”
Section: Introductionmentioning
confidence: 75%
“…However, with one exception of all the 19 included randomized controlled trials investigated longer and/or more frequent yoga programs. Concerning HRV, two recent studies (45,46) also reported positive outcomes, however both applied longer yoga interventions. Thus, we can assume that although yoga may affect HR and HRV positively, 10 weekly sessions are not sufficient to evoke such changes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most studies indicate that physical therapy for women after breast cancer surgery might significantly improve the upper limb condition [20], heart rate variability [21], functional state of the cardiopulmonary system [22][23][24], and quality of life. Theoretical justification for the use of yoga therapy for women's health [25], especially for patients with breast cancer, was based on its positive impact reported in scientific studies [6][7][8][9] on the functioning of the upper extremity, cardiovascular system, emotional state, quality life, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was conducted to evaluate the impact of hatha yoga intervention on the cardiovascular system in patients after breast cancer surgery. Most previous yoga programs for patients with breast cancer have been performed to reduce cancer treatment-related symptoms such as fatigue, heart rate variability, lymphoedema, depression, anxiety, and poor quality of life [17][18][19]30]. Some previous studies have identified that yoga considerably impacts on cardiorespiratory fitness and strength in healthy adults [31][32][33], but hatha yoga effect on functional capacity of the cardiovascular system in breast cancer Ukrainian patients has not been reported.…”
Section: Discussionmentioning
confidence: 99%